1989
DOI: 10.1093/nar/17.20.8185
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a pancreatic nuclear protein is correlated with amytase enhancer activity

Abstract: The mouse amylase gene Amy-2.2 is expressed at high levels specifically in the acinar cells of the pancreas. The region between -172 and -110 of this gene includes sequence elements common to pancreas-specific genes. Nuclear proteins with specific affinity for this region were partially purified from rat pancreas. The consensus element of another pancreas-specific gene, elastase 1, competes for protein binding to the amylase sequences. Binding was localized by DNase I protection to the sequence -156 to -122. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…This region of the mouse gene contains an enhancer element which is recognized by the pancreas-specific nuclear protein PTF1 (3,13). The rodent PTF1-binding sites are aligned with the human genes in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This region of the mouse gene contains an enhancer element which is recognized by the pancreas-specific nuclear protein PTF1 (3,13). The rodent PTF1-binding sites are aligned with the human genes in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the region between À2300 and À1 bp of C57BL/6J mice was similar to that of C3H mice. Three binding sites were found in the 1 kb upstream region of the Prss1 gene 31,37 (Supplementary Figure 3). All these sequences are identical in all strains except one nucleotide change at À192 of the binding site (ATCACCTGCT) for nuclear protein in JF1 mice.…”
Section: Nucleotide Sequences Of 3 Kb Upstream Regions Of Spink3 and mentioning
confidence: 99%
“…1987). Comparison between the 5'-flanking regions of nine genes expressed in both the rat and mouse exocrine pancreas resulted in the identification of a family of short, related sequences located within the enhancer regions of these genes (Walker et al 1983;Swift et al 1984; Boulet et al 1986;Stevenson et al 1986;Howard et al 1989). Site-directed mutagenesis studies showed that these cis-acting sequences are actually involved in regulating the expression of tissue-specific genes through the binding of the specific pancreatic nuclear protein PTF1.…”
mentioning
confidence: 99%